Annual Plan 1997-98 Volume- I Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1997)
The total area of flat land available for paddy cultivation is limited to 12000 hect. and there exists a little scope for further expansion of area. This available 12000 hect. are utilised for cultivation of paddy, pulses, oilseeds, vegetables etc. The paddy is grown as rainfed crop and scope for raising a second crop of paddy is very much limited due to non availability of irrigation facilities. Pulses, oilseeds, vegetables etc. are being grown in paddy fallows while tuber crops and sugarcane as mono crops in limited scale.
Andaman and Nicobar Administration
Andaman and Nicobar Administration